ChemInform Abstract: Visible‐Light‐Activated Molecular Switches. Issue 46 (November 2015) - Bleger, David; Hecht, Stefan
Abstract Review: [conceptual strategies for the design of photochromic compounds that can be toggled between their two switching states by employing only low‐energy visible (or near‐infrared) light; 89 refs.